Resistance of non-fermenting Gram-negative bacilli isolated from blood cultures from an emergency hospital - Marcelo Eduardo F. Oliveira; Danielle G. Araújo; Sibele R. Oliveira (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: Non-fermenting Gram-negative bacilli (NFGNB) are a heterogeneous group of microorganisms that do not have the ability to ferment carbohydrates as a way to obtain energy. There are more than 120 species classified as pathogenic, among them, Pseudomonas aeruginosa, Acinetobacter baumannii, Stenotrophomonas maltophilia and Burkholderia cepacia. Infections caused by these microorganisms are mostly acquired in the hospital environment, since they are opportunistic pathogens and are among the most important bacteria of greater clinical and epidemiological relevance. Objective: This study evaluated the resistance profile of NFGNB isolated from blood cultures at an emergency hospital in the city of Caruaru, Agreste Pernambuco (PE), Brazil. Methods: The strains present in the blood cultures were isolated on culture media MacConkey and Triple Sugar Iron (TSI) agar. The samples were also submitted to the oxidase test and the polymyxin resistance test, in addition to the Gram staining, to better identify NFGNB bacterial genera. An antibiogram test was carried out to verify the resistance profile. Results: It was found that from 87 (100%) isolated and analyzed strains, 11 (13%) were classified as NFGNB. The genus Acinetobacter sp. was the most frequently found (55%). The Acinetobacter sp. strains were resistant to gentamicin, meropenem, imipenem, amikacin, ciprofloxacin, ceftazidime and ceftriaxone. Conclusion: Screening of resistant NFGNB isolated, as well as greater attention to hospital-acquired infection control practices and epidemiological surveillance systems, in addition to continued care with regard to the targeted use of antibiotics can contribute to successful this battle against infections by these microorganisms.